Molecular Structure, Pathogenesis and Virology of SARS-CoV-2: A Review - Akram, Arifa; Mannan, Nusrat (Bangladesh Journal of Infectious Diseases, 2020)
SARS-CoV-2 or 2019 n-CoV is a newly identified coronavirus which has a high similarity with SARS CoV. The emergence of SARS-CoV-2 has resulted about 1850220 cases and 114215 deaths worldwide up to 13th April, 2020. The clinical criteria of SARS-CoV-2 pneumonia range from mild to critically ill cases. To characterize and control the disease, Chinese authorities did an immediate investigation, including isolation of suspected people, close monitoring of contacts, epidemiological and clinical data collection from patients, and development of diagnostic and treatment procedures. SARS-CoV-2 poses a significant public health risk for human transmission via the S protein–ACE2 binding pathway. It’s spike (S) glyco protein promotes entry into cells. To date, the SARS-CoV-2 genome has been considered genetically more stable than other pandemic viruses like SARS-CoV or MERS-CoV. The rapid global spread of 2019-nCoV, which prompted the PHEIC declaration by WHO, signals the urgent need for corona virus vaccines and therapeutics. Bangladesh Journal of Infectious Diseases, April 2020;7(suppl_1):S36-S40